THE COMPETENCE OF TEACHERS IN MODERN EDUCATION - Požar, Hajnalka F (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2017)
Daily changes in all areas of human activity have made changes in the demands that are put before teachers.  Teachers in addition to their primary area of ​​work, have to adapt and fit into the paradigm of the modern schools and teaching. The aim of this paper is to analyze the desirable competencies of teachers as well as teaching basic assumptions for the advancement of teaching. In this concept, the paper analyzes the competences and the role of teachers in modern schools, their ability to apply modern teaching and educational innovations, which tend to overcome the traditional ways of teaching and to contribute to active teaching in terms of performance training of future generations of teachers which requires a wide array of competencies.  The fate of future generations is in their hands, and a lot can be done so that this generation can develop specific knowledge and skills, to be adequately prepared for life and to work in modern society.
Keywords: modern school; TEACHERS; competence